Two theorems in the theory of summation of numerical series by lower triangular positive monotone matrices - Davydov, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For so-called monotone matrices, we establish necessary and sufficient conditions for the summation with them of some divergent sequences of 0 and 1 up to zero or some unbounded sequences of nonnegative numbers.